Buszel, Kombajner, and Rels: Fisiak’s 1961 Corpus of English Borrowings in Polish Fifty Five Years Later - Dylewski, Radosław (Studia Anglica Posnaniensia, 2016)
The onset of Professor Jacek Fisiak’s scholarly career is marked by his 1961 Ph.D. dissertation devoted to the lexical influence of English upon Polish. This study, conducted 55 years ago, offers a multilayered analysis and sets the standards of studies on lexical transfer from English to Polish for the years to come. The present article is a tribute to Fisiak’s first scholarly endeavor; it examines the fate of lexical items comprising Fisiak’s corpus in the second decade of the 21st century. More specifically, by conducting searches in the National Corpus of Polish as well as a Google search, the paper checks which borrowings to the Polish language listed and scrutinized by Fisiak gained popularity, which fell out of use, and which underwent semantic changes.